Studies on Water-Polymer Interactions inthe Presence of Aceclofenac at 298.15 K - Siti S. B. Ambomase; Sushree Tripathy; Minaketan Tripathy; Upendra N. Dash (E-Journal of Chemistry)
Densities and ultrasonic velocities of aqueous mixtures of methyl cellulose (MC) and polyethylene glycol (PEG) and of methyl cellulose and hydroxyl propyl methyl cellulose (HPMC), over the compositions, 9:1, 8:2 and 6:4, and of MC, HPMC and PEG, over the compositions, 9:0.5:0.5, 8:1:1 and 6:2:2, have been measured with and without acelofenac at 298.15K and at atmospheric pressure. The experimental ultrasonic velocities have been used to determine isentropic compressibilities, apparent isentropic molar compressibilities, acoustic impedance, molar compressibility, molar sound velocity, free volume and relative association for the systems with and without aceclofenac. The results have been discussed in terms of solute solvent and solute-solute interactions and various structural effects.